Badania klimatu akustycznego na terenach rekreacyjno-wypoczynkowych = Acoustic climate study in recreation and leisure area - Sztubecka, Małgorzata; Sztubecki, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper includes an assessment of noise pollution in the spa park area, which was based on differences analysis between actual results of equivalent sound level and the spa park visitors feelings. The results of questionnaires were statistically analyzed and the fuzzy sets theory. Interpretation of the results has shown that the assessment of the spa park acoustic climate should be determined on the basis of sound level measurements and questionnaires. The fuzzy model is appropriate for this type of observation.
Keywords: zanieczyszczenie powietrza; hałas; tereny zielone; analiza rozmyta; air pollution; noise; green areas; fuzzy sets